Feeding Broodstock on a Diet Containing Vitamin E and Fish Oil Improve Eggs and Larval Quality of Nile tilapia (Oreochromis niloticus) - S. Darwisito; M. Zairin Junior; D.S. Sjafei; W. Manalu; A. Oman Sudrajat (Jurnal Akuakultur Indonesia)
The experiment was conducted to determine the effect of dietary vitamin E and n-3 fatty acids on the gonad maturation, egg and larva quality of Nile tilapia. Fish were treated by various combinations of dietary dosage of vitamin E (50, 100, 150, and 200 mg/kg feed) and fish oil (10, 20, 30, and 40 g/kg feed). Three hundreds and twenty pairs of broodstock fish (female at stage of maturity II) were selected and used for this experiment. Fish were fed on the experimental diets three times a day at satiation. The tested of parameters such as gonad somatic index, egg diameter, fecundity, number of spawned fish, hatching rate, and survival rate. Results of the experiment indicated that supplementation of vitamin E and fish oil stimulated gonad development and increased fecundity, hatching rate and survival rate of Nile tilapia larva. Combination of vitamin E 150 mg/kg feed and fish oil 30 g/kg feed significantly improved egg and larva quality of Nile tilapia. Thus, combination of vitamin E in 150 mg/kg diet with fish oil in dose 30 g/kg diet give the best reproduction performance.